Microwave assisted "coffee effect" synthesis of spherical and porous spherical nano aluminum hydroxide - Wu, Zhifu; Xu, Qin (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
AlNH4(SO4)2·12H2O was dissolved in the mixture of ethanol and glycol, then spherical and porous Al(OH)3nanoparticles were synthesized by microwave heating at different temperatures. The products were characterized by XRD and SEM, and the formation process was analyzed by coffee effect.